Solution concentration sensor based on organicsemiconductor and its potential applications - Zhao, Chongyang (My University, 2020)
From the emerging of the semiconductor industry to the present, mainly inorganic elements are used to make semiconductor devices. These materials have advantages in performance and lifetime, but their fabrication processes are complicated. Besides, such inorganic transistors are approaching physical limits. Low-dimensional materials and organic semiconductor materials are promising semiconductor materials, because of simple manufacturing processes and easy processing into large-area flexible devices, suitable for producing wearable devices and sensors.Solutions in detection of concentration of substances are often based on either chemical reactions or physical quantities. Methods are complex, and difficult to integrate into a portable system. To meet the demands of the Internet of Things and wearable devices developments, development of new low-cost sensors with low-energy consumption is essential.In this thesis, an optoelectronic sensor based on P3HT:PCBM (poly(3-hexylthiophene):phenyl-C61-butyric acid methyl ester) material organic semiconductor co-planar structure is made for detection of non-electrolyte concentrations in aqueous solution. The structure, working principle, fabrication process and characterization of the device are described in detail. The response current of the sensor decreases linearly with increasing concentrations of glucose and glycerol in aqueous solutions. The sensor using Al/Au electrode and the excitation light wavelength of 520 nm is more sensitive.Based on sensor response, combined with some understanding of neuroscience, it is proposed here a neural signal simulation device of optical pulse stimulation. The response current of such a device can be controlled by the thickness of the organic semiconductor layer or the wavelength of the excitation light.

从半导体工业产生到现在，用来制作半导体器件的材料主要是硅和锗等无机元素及其化合物。这类材料制作的半导体器件虽然在性能和寿命上有很大优势，但是其制作工艺复杂，并且随着晶体管的尺寸逼近物理极限这类材料很有可能被未来的半导体产业抛弃。目前有很多的研究结果表明低维材料和有机半导体材料是未来半导体材料发展的方向。其中有机半导体材料具有制作工艺简单，易加工成大面积柔性器件等优点，使得这类材料非常适合制作可穿戴设备以及传感器。目前的主流的溶液浓度检测是利用物质间的化学反应或者检测与浓度相关的其他物理量来获得浓度值，这些方法大都比较复杂，很难集成到一个便携式的系统中。因此，为了满足物联网和可穿戴设备发展的需求，开发集成度高，低功耗，低成本的新型传感器非常有必要。 本文提出了一种基于P3HT:PCBM材料的有机半导体平面结构的光电器件，可以用于非电解质水溶液的浓度检测。文章首先简述了有机半导体的发展过程，并介绍了该浓度传感器的结构和工作原理。之后又详细介绍了这种器件的制作工艺和流程以及表征方法。通过对实验数据的分析得出以下结论。对于葡萄糖和甘油这类容易在水溶液中形成氢键的非电解质来说，器件的响应电流与这类物质在水溶液中的浓度成反比。通过对比波长为520 nm和635 nm的激发光作用下器件的响应可以发现，以这两种激发光为工作光源，器件的响应变化趋势相同，但是520 nm的激发光作用下这种传感器对溶液浓度的响应更加灵敏。出现这一现象是因为器件中使用的有机半导体材料对520 nm波长的光波吸收系数比635 nm光波高。此外，通过对比同相同结构下不同电极材料器件的响应发现，Al/Au电极对器件的电流响应比ITO/Au电极对器件高，这是因为前者有更高的电极功函数差导致。 根据浓度传感器器件响应的特点，并结合一些对神经科学的了解，本文提出了一种光脉冲刺激的神经信号模拟器件。通过实验发现，这种器件的响应电流可以被有机半导体层的厚度或者是激发光的波长控制。其响应电流的变化类似与神经元中的兴奋和抑制信号，因此它具有作为神经计算和神经信号模拟的可能性。 本文通过对P3HT:PCBM有机半导体平面结构器件工作原理和实验结果的分析验证了其作为溶液浓度传感器的可行性，并且提出了这种结构的器件在神经信号模拟方面的潜在应用。
Keywords: organic semiconductor,photoelectric device,solution concentration sensor,neuromorphic computing